Structure of Li5AlS4 and comparison with other lithium-containing metal sulfides - Lim, Hanjin; Kim, Sung Chul; Kim, Jaegyeom; Kim, Young Il; Kim, Seung Joo (Journal of Solid State Chemistry, 2018)
Lithium aluminum sulfide (Li5AlS4) was synthesized by solid state reaction, and its crystal structure was characterized by ab initio structure determination on the basis of powder neutron diffraction (ND) data. Li5AlS4 was found to have monoclinic unit cell (space group, P21/m) with the lattice parameters: a = 6.8583(4) Å, b = 7.8369(4) Å, c = 6.2488(4) Å, and β = 90.333(4)°. This structure is built from a hexagonal close-packed (hcp) arrangement of sulfur atoms with a stacking sequence of …ABAB…. The hcp sulfide lattice consists of two different double-sulfide layers alternately stacked along the c-axis. Between the first pair of sulfur layers all the tetrahedral interstices (T+ and T- sites) are filled with lithium and aluminum atoms. All octahedral interstices between the second pair of sulfur layers are occupied by the remaining lithium atoms. The structure of Li5AlS4 is compared with those of various lithium-containing metal sulfides like Li2FeS2, NaLiMS2 (M = Zn, Cd), Li4GeS4, LiM′S2 (M′ = Al, Ga, In) and γ-Li3PS4. Each sulfide represents a specific distribution of lithium atoms in the lattice depending on how the octahedral and tetrahedral interstitial sites are filled. The low ionic conductivity of Li5AlS4 (9.7 × 10−9 S cm−1 at 323 K) relative to other sulfides may be due to the highly-ordered distribution of the lithium atoms in the layered structure and the lack of adjacent void spaces that can be used for lithium ion hopping.
Keywords: Ab initio structure; Hexagonal close packed; Layered Structures; Metal sulfides; Octahedral interstices; Powder neutron diffraction; Specific distribution; Tetrahedral interstices; Crystal structure; Ionic conductivity; Lithium-containing metal sulfide; Neutron diffraction; Structure description